Manufacturing constraints in parameter-free sensitivity-based shape optimization - Schmitt, Oliver; Friederich, Jan; Steinmann, Paul (Proceedings of 1st International Conference on Engineering and Applied Sciences Optimization, 2014)
Structural shape optimization has become an important tool in engineering when it comes to improving components with respect to a given cost function. However, in many applications the designer has to ensure that the optimized part is still manufacturable. This work introduces two approaches on how to handle manufacturing constraints in parameter- free sensitivity-based shape optimization. In the so-called implicit method the set of design nodes is split into two groups of optimization nodes and dependent nodes. The optimization nodes are then handled as design nodes, whereas the dependent nodes are coupled to the optimization nodes in such a way that the manufacturing constraint is fulfilled. By that procedure no additional constraints have to be appended to the optimization problem. When no dependency can be determined additional equality and inequality constraints have to be formulated in terms of the coordinates of the design nodes. In this case the formulation of manufacturing constraints may lead to a large number of inequalities. Since most optimization algorithms are not able to handle highly restricted problems the use of aggregation formulations is investigated.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-TM.manufa_0
Keywords: Manufacturing constraints; Parameter-free; Sensitivity-based; Shape optimization